2011
DOI: 10.1093/ije/dyr077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at CHRNA5-CHRNA3-CHRNB4 interacts with smoking status to influence body mass index

Abstract: Background Cigarette smoking is associated with lower body mass index (BMI), and a commonly cited reason for unwillingness to quit smoking is a concern about weight gain. Common variation in the CHRNA5-CHRNA3-CHRNB4 gene region (chromosome 15q25) is robustly associated with smoking quantity in smokers, but its association with BMI is unknown. We hypothesized that genotype would accurately reflect smoking exposure and that, if smoking were causally related to weight, it would be associated with BMI in smokers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
98
6
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 43 publications
15
98
6
3
Order By: Relevance
“…Although there was no evidence of association between variation at rs1051730 and BMI in never smokers, each additional risk allele (T) was associated with a BMI decrease of 0.16 and 0.33 kg/m 2 among former and current smokers respectively [165]. A separate study of 14131 Pakistani adults reported another gene × smoking interaction: the minor allele (T) in FLJ33534 was associated with lower BMI in current smokers and positively associated with BMI among adults who had never smoked [166].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 72%
See 1 more Smart Citation
“…Although there was no evidence of association between variation at rs1051730 and BMI in never smokers, each additional risk allele (T) was associated with a BMI decrease of 0.16 and 0.33 kg/m 2 among former and current smokers respectively [165]. A separate study of 14131 Pakistani adults reported another gene × smoking interaction: the minor allele (T) in FLJ33534 was associated with lower BMI in current smokers and positively associated with BMI among adults who had never smoked [166].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 72%
“…A meta-analysis of nine European study samples (n = 24198) demonstrated that smoking status moderated the association between genetic variation at the CHRNA5-CHRNA3-CHRNB4 locus (rs1051730) and BMI [165]. Although there was no evidence of association between variation at rs1051730 and BMI in never smokers, each additional risk allele (T) was associated with a BMI decrease of 0.16 and 0.33 kg/m 2 among former and current smokers respectively [165].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 99%
“…Another potential explanation is the indirect effect of smoking on lifestyle factors such as BMI. Increasing BMI is an established risk factor for OA and subsequent TJR 26,27 and there is evidence to suggest that smoking may lead to lower BMI 18,28,29 , which could mediate the effect of smoking on TJR 30 . However, the association of rs1051730 T alleles with TJR was only slightly attenuated after statistical adjustment for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gene variants with which individuals are born should not be altered by environmental factors, such as the outcome of interest, which removes the issue of reverse causality. This approach has been used to examine the causal impact of cigarette smoking on a variety of health outcomes 5, 6, 7. The identification of genetic variants associated with coffee consumption 8, 9, 10, 11, 12 presents the opportunity to use MR to examine the causal impact of coffee consumption on smoking.…”
Section: Introductionmentioning
confidence: 99%